Insect pollinators collect pollen from wind‐pollinated plants: implications for pollination ecology and sustainable agriculture. Issue 1 (24th June 2017) - Saunders, Manu E.
Abstract: Current research, management and outreach programmes relevant to insect pollinator conservation are strongly focused on relationships between pollinators and insect‐pollinated crops and wild plants. Pollinators also visit wind‐pollinated plants to collect pollen, or for nest sites and materials, but these interactions are largely overlooked. I review documented records of bee and syrphid fly species collecting pollen from wind‐pollinated plant taxa, including economically important crops, and provide the most comprehensive collation of peer‐reviewed records of pollinators visiting wind‐pollinated plants to date. I argue for more basic research into functional relationships between insect pollinators and wind‐pollinated plants. I found over 200 visitation records for 101 wind‐pollinated plant genera in 25 families, including 4 of the 12 gymnosperm families. Almost half the records (49%) were for grasses and sedges (Poales). I also identified records of bees and/or syrphid flies visiting 10 economically important wind‐pollinated crop plant species, including three major grain crops (rice, corn, and sorghum). Most records (70%) were from indirect pollen analysis from hives, nest cells or insect bodies, highlighting the need for more direct observational studies of plant–pollinator interactions. Insect pollinator communities require resource diversity to persist in a landscape. Hence, researchers and land managers aiming to identify links between pollinators and ecosystem function should also consider broader interactions beyond the standard traits of the entomophily syndrome.